PENGEMBANGAN MULTIMEDIA BERBASIS POWTOON PADA TEMA 1 SUBTEMA 2 PEMBELAJARAN 1 MANUSIA DAN LINGKUNGAN DI KELAS V SEKOLAH DASAR - Rizki Andani, Mifta Tri; Yenny Puspita; Maharani Oktavia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to lead to the development of multimedia-based powtoon learning theme 1 subtheme valid 2 practical on Human and Environmental materials in V primary school class. Research and Devolopment was developed using thw ADDIE (Analyze, Design, Devolopment, Implementation, Evalation) and data collection techniques used in the from of pickets, obsevations, and data collection techniques. Documentation The data analysis techniques is carried out by conducting validation analysis using a validation spreadsheet, by 3 experts who assess in terms of material, meda and language. Meanwhile, for practicality analysis by usisng student response sheet by 15 students, namely 6 students in the One-to-One method and 9 students in the Small Group method. The results of the analysis obtained from the development of powtoon-based multimedia on theme 1 subtheme 2 of study 1 were stated “Very Valid” based on the results of assessments by experts, namely media experts at 93,3%, from material experts at 93,3% and 82%, respectively. Linguists of 82% and for the practicality of powtoon-based multimedia on theme 1 subtheme 2 human and environmental studies were declared “Very Practical” based on results on the one-to-one method of 88,3% and the small group method of 89,1%.